The Peculiarities of Visibility in The Pedagogical Process - Salimova Nilufar Aminjon qizi (Academia One Publishing, 2024)
This article reveals about visibility in the classroom that helps students form ideas that correctly reflect objective reality through the recognition of objects and processes in the environment, while at the same time analyzing the perceived phenomena in the context of the educational task and understanding the general public.It is mentioned about the principle of visibility, visual teaching and the importance of modern technologies in education. This article can be useful for researchers and pedagogical access
Keywords: visibility; principle; teaching